INTERTEXTUALITY IN THE NOVELS OF ORHAN PAMUK - Tuan Anh Pham (Tạp chí Khoa học Đại học Đà Lạt, 2024)
This study focuses on interpreting intertextuality in the novels by Orhan Pamuk in terms of dialogue with Turkish historical, cultural, and social discourse, focusing on mechanisms of intertextual citation and the integration and mixing of genres. Research results show that his novels address many issues in the social life of Turkey, a country with extremely important geopolitics, acting as a bridge for Eastern and Western cultural interference and dialogue. Recreating a chaotic hyperreality, Pamuk reveals his sense of humanity in modern life. The mechanisms of intertextual citation and integration and mixing of genres are fully utilized by Pamuk to expand the dimension of reality, increase openness, and continuously generate meaning for the text. Based on the analysis of intertextuality in Pamuk’s novels, this study provides both theoretical and practical insights that open up a framework for reference regarding the current state of literary research and creation in Vietnam.